Analysis of the Realities, Evolution and Prospects of Urban Greening from an International Point of View - Fernando Barriuso; Beatriz Urbano (Amfiteatru Economic)
There is an increasing concern about the imbalance between urbanisation and environmental conservation, with over half of the world’s population living in urban environments. Therefore, urban greening aims to incorporate nature into the city, recovering native flora in a sustainable way. Urban greening is a multi-functional environmental benefit system that incorporates vegetation in urban cores. Urban greening has become one of the most innovative and rapidly developing fields in ecology, green procurement and the built environment. The aim of this study was to provide an insight into the realities, evolution and prospects of urban greening from an international point of view. A sample of 1,727 worldwide urban greening projects was analysed, a Pearson’s chi-square test was used to study the evolution of urban greening, and a binary logistic regression was used to predict determinant factors of public urban greening. Results show urban greening is prevalent in well-developed urbanised cities, while is challenging in the world's fastest growing cities in low-income countries. Urban greening installation has significantly changed from intensive to extensive systems offering the most cost-effective solution, and currently to living walls due to the emergence of this technology. Urban greening has expanded significantly from university campuses and parks, for the general public’s benefit, to streets for families’ use. The urban greening projects were installed mainly in private, residential, commercial, educational and government buildings. The main motivations of urban greening projects were environmental or aesthetic purposes and research aims. The prospects show parks and for general public are determinant factors for public urban greening at global level. This study contributes to the literature by investigating the characteristics and evolution of urban greening systems and prospects of public urban greening from an international point of view